Voicing youth empowerment: Critical discourse analysis on Joshua SEVENTEEN speech at UNESCO Youth Forum 2023 - Aila Maisya (Universitas Pakuan, 2026)
This study analyzes Joshua’s speech, a member of the K-pop group SEVENTEEN, at the UNESCO Youth Forum 2023 using Teun A. Van Dijk’s Critical Discourse Analysis framework. The research investigates how discourse structures in public speeches convey messages of education and youth empowerment. A qualitative descriptive method was applied to examine macrostructure, superstructure, and microstructure. The findings show that the macrostructure emphasizes education as a transformative force; the superstructure presents a well-organized format aligned with international speech conventions; and the microstructure employs semantic clarity, inclusive syntax, stylistic consistency, and rhetorical devices such as metaphors and hashtags to build emotional resonance with global youth. Audience reactions on YouTube were further analyzed through the Stimulus-Organism-Response (S-O-R) theory, demonstrating pride, awareness, and affective engagement. The study concludes that Joshua’s speech successfully conveyed educational values and inspired global participation, affirming that popular culture figures can act as effective agents of social change through discourse.